Farming model of the crop livestock system in the paddy field is located at Cianjur Distric. The crop livestock system is an effort to increase rice production that be integrated with livestock. The purpose of the assessment was to find out the role of cattle on the farmer income through the integrated farming system based on the technology innovations on Cianjur district. The integration pattern was the utilization of plant straws as feed and manure for fertilizer. Integrated farming system - Ruli Basuni; Muladno Basar; Cecep Kusmana; Suryahadi . (Forum Pasca Sarjana, 2010)
Farming model of the crop livestock system in the paddy field is located at Cianjur Distric. The crop livestock system is an effort to increase rice production that be integrated with livestock. The purpose of the assessment was to find out the role of cattle on the farmer income through the integrated farming system based on the technology innovations on Cianjur district. The integration pattern was the utilization of plant straws as feed and manure for fertilizer. Integrated farming system that has been introduced are paddy planting, livestock fattening, and paddy straw fermentation for food and also ecreement of livestock for organic fertilizer processing. The assessment involved livestock and 5 ha paddy planting area. The farmer consist of 2 groups ie.: 20 cooperator group (integrated system), and 10 control (non integrated). The assessment results showed that rice yield was 5.34 tons/ha of dried ground rice, an increase of 16.09% compared to those yielded by other farmers. The use of inorganic fertilizer decreased urea to 100 kg/ha (N 71.43%), SP-36 50 kg/ha (50%), KCl 50 kg/ha (50%). The average of daily weight gain was 0.89 kg/cattle daily. The income of farmers with the integrated farming system was Rp 9,417,907 for ones hectare land and 2 beef cattle with R/C ratio of 1.27. The average organic fertilizer yielded was 5 kg/cattle daily, the rice straw yielded was 13.20 tons/ha/year. The C/N ratio of composted feces was 19.03%. Total income from paddy (5 ha) and livestock (20 heads) integrated farming system about Rp 24,867,500 and Rp 60,675,333/season and provide R/C value about 1.44, meanwhile R/C value of non integrated farming system about 1.33. It means, paddy and livestock integrated farming system could increase farmer’s income about 69,45% per season compared to non integrated farming. Key words: integration, paddy, livestock, fermentation